1977
DOI: 10.1017/s0022112077001189
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental investigations of two-dimensional nonlinear peristaltic flows

Abstract: An implicit finite-difference technique employing orthogonal curvilinear co-ordinates is used to solve the Navier–Stokes equations for peristaltic flows in which both the wall-wave curvature and the Reynolds number are finite (§2). The numerical solutions agree closely with experimental flow visualizations. The kinematic characteristics of both extensible and inextensible walls (§3) are found to have a distinct influence on the flow processes only near the wall. Without vorticity, peristaltic flow observed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 9 publications
1
69
0
1
Order By: Relevance
“…Brown and Hung (1977) claimed also that this trend reverses for finite amplitude to wavelength ratios, Finally, our experimental results suggest also a weak dependence of oral residues on bolus volume. Splitting a bolus in several smaller volumes could therefore increase the cumulated residual mass.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Brown and Hung (1977) claimed also that this trend reverses for finite amplitude to wavelength ratios, Finally, our experimental results suggest also a weak dependence of oral residues on bolus volume. Splitting a bolus in several smaller volumes could therefore increase the cumulated residual mass.…”
supporting
confidence: 68%
“…Another mechanism that could explain the residue increase when high viscosity liquids are swallowed, is a reduced effectiveness of the peristaltic flow. Brown and Hung (1977) considered the steady viscous flow induced by a peristaltic wave in a bi-dimensional channel.…”
mentioning
confidence: 99%
“…In the case of a very flexible membrane, such as the one considered in this study, the drag force has been shown in Takagi and Balmforth (2011) to be provided purely by the fluid pressure and determined by the flow within the bolus. While Hayoun et al (2015) have considered a linear dependency of F d in ω, other studies (Brown and Hung, 1977;Takabatake and Ayukawa, 1982) have shown that this is valid only at low Reynolds numbers Re. At higher Re (typically reached for lower viscosity liquids), it becomes necessary to account for inertial effects in the fluid.…”
mentioning
confidence: 99%
“…Later studies on the subject extended the previous ones to include inertial effects, 5,6 high Reynolds number effects, 7,8 creeping flow condition, 9 effects of peripheral layers 10 etc. The non-Newtonian nature of biological and industrial fluids is also incorporated in the studies on peristaltic transport.…”
Section: Introductionmentioning
confidence: 99%